Holocene glacier fluctuations. (1st March 2015) - Solomina, Olga N.; Bradley, Raymond S.; Hodgson, Dominic A.; Ivy-Ochs, Susan; Jomelli, Vincent; Mackintosh, Andrew N.; Nesje, Atle; Owen, Lewis A.; Wanner, Heinz; Wiles, Gregory C.; Young, Nicolas E.
Abstract: A global overview of glacier advances and retreats (grouped by regions and by millennia) for the Holocene is compiled from previous studies. The reconstructions of glacier fluctuations are based on 1) mapping and dating moraines defined by 14 C, TCN, OSL, lichenometry and tree rings (discontinuous records/time series), and 2) sediments from proglacial lakes and speleothems (continuous records/time series). Using 189 continuous and discontinuous time series, the long-term trends and centennial fluctuations of glaciers were compared to trends in the recession of Northern and mountain tree lines, and with orbital, solar and volcanic studies to examine the likely forcing factors that drove the changes recorded. A general trend of increasing glacier size from the early–mid Holocene, to the late Holocene in the extra-tropical areas of the Northern Hemisphere (NH) is related to overall summer temperature, forced by orbitally-controlled insolation. The glaciers in New Zealand and in the tropical Andes also appear to follow the orbital trend, i.e., they were decreasing from the early Holocene to the present. In contrast, glacier fluctuations in some monsoonal areas of Asia and southern South America generally did not follow the orbital trends, but fluctuated at a higher frequency possibly triggered by distinct teleconnections patterns. During the Neoglacial, advances clustered at 4.4–4.2 ka, 3.8–3.4 ka, 3.3–2.8 ka, 2.6 ka, 2.3–2.1 ka, 1.5–1.4 ka, 1.2–1.0 ka, 0.7–0.5 ka, corresponding to general cooling periods in the North Atlantic. Some of these episodes coincide with multidecadal periods of low solar activity, but it is unclear what mechanism might link small changes in irradiance to widespread glacier fluctuations. Explosive volcanism may have played a role in some periods of glacier advances, such as around 1.7–1.6 ka (coinciding with the Taupo volcanic eruption at 232 ± 5 CE) but the record of explosive volcanism is poorly known through the Holocene. The compilation of ages suggests that there is no single mechanism driving glacier fluctuations on a global scale. Multidecadal variations of solar and volcanic activity supported by positive feedbacks in the climate system may have played a critical role in Holocene glaciation, but further research on such linkages is needed. The rate and the global character of glacier retreat in the 20th through early 21st centuries appears unusual in the context of Holocene glaciation, though the retreating glaciers in most parts of the Northern Hemisphere are still larger today than they were in the early and/or mid-Holocene. The current retreat, however, is occurring during an interval of orbital forcing that is favorable for glacier growth and is therefore caused by a combination of factors other than orbital forcing, primarily strong anthropogenic effects. Glacier retreat will continue into future decades due to the delayed response of glaciers to climate change. Graphical abstract: Highlights: Northern Hemisphere mid-low latitude Holocene glaciation driven by orbital forcing. Neoglacial advances correspond to multidecadal periods of low solar activity. Current glacier retreat unlikely be explained only by natural forcings.